2020
DOI: 10.1039/c9tc06509a
|View full text |Cite
|
Sign up to set email alerts
|

The optical signatures of molecular-doping induced polarons in poly(3-hexylthiophene-2,5-diyl): individual polymer chainsversusaggregates

Abstract: For molecularly doped poly(3-hexyl-thiophene) solvated individual chains can be unambiguously differentiated from aggregated ones by diagnostic polaron absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 49 publications
2
77
0
Order By: Relevance
“…However, although the structureless feature is consistent with that expected for the "protonated radical", it could also in principle arise from dynamic effects leading to loss of the structure expected for the polaron signal, or even from other radicals formed through side reactions. We also reckon that, as observed elsewhere in the literature, 24,[49][50][51] the polymer conjugation length plays a paramount role in the context of molecular doping, since different mechanisms might occur depending on the extension of the polymer backbone. To address this point, Table S6 in ESI ‡ reports the computed DH 0 elec values pertaining to Scheme 1 and Scheme 2, using either a PCPDTBT tetramer or an octamer as representative model.…”
Section: Resultsmentioning
confidence: 66%
“…However, although the structureless feature is consistent with that expected for the "protonated radical", it could also in principle arise from dynamic effects leading to loss of the structure expected for the polaron signal, or even from other radicals formed through side reactions. We also reckon that, as observed elsewhere in the literature, 24,[49][50][51] the polymer conjugation length plays a paramount role in the context of molecular doping, since different mechanisms might occur depending on the extension of the polymer backbone. To address this point, Table S6 in ESI ‡ reports the computed DH 0 elec values pertaining to Scheme 1 and Scheme 2, using either a PCPDTBT tetramer or an octamer as representative model.…”
Section: Resultsmentioning
confidence: 66%
“…Recently, it was clarified that the observation of one P2 feature indicates the presence of weakly interacting individual P3HT chains, whereas it is split into P2 a and P2 b in P3HT (crystalline) aggregates due to interchain interactions. [59] Apparently, with B(C 6 F 5 ) 3 as dopant, P3HT can still form these aggregates in films up to 50% dopant loading (with dopant anions residing in the periphery of aggregates), while aggregation is significantly suppressed for 80% loading. Yet, up to 50% dopant concentration the polaron features do not shift.…”
Section: Indications For Bipolarons From Optical Absorption and Condumentioning
confidence: 96%
“…The absence of ground-state charge transfer in 4T:BCF, modeled here as an isolated bimolecule in vacuo, is in perfect agreement with a previous calculation performed in an idealized thiophene polymer doped by BCF. 35 This finding reveals that the doping mechanism between 4T and BCF does not result from direct charge transfer, but is driven by external factors, such as polaron formation, integer charge transfer with consequent protonation of the donor, and solution environment 27,34,35,61 that are not included in these calculations. Figure 2: Level alignment, computed from G 0 W 0 , of (a) 4T:BCF (b) 4T:C 6 F 6 (c) 4T:BF 3 , with respect to their constituents: The frontier states of the acceptors are referred to the gas-phase molecule, while for 4T we report both the frontier energies in the isolated molecule (4T iso ) and in the distorted geometry of the adduct.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…[17][18][19] The emergence of Lewis acids like tris(pentafluorophenyl)borane, B(C 6 F 5 ) 3 (in short BCF) 20,21 as novel dopant species has opened new routes for efficient p-doping of organic polymers and oligomers. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] The pioneering study by Pingel et al, 27 has identified integer charge transfer between poly(3-hexylthiophen-2,5-diyl) (P3HT) and BCF, but has not been able to fully disclose the underlying physical processes. The recent work by Yurash et al 34 has demonstrated that the doping mechanisms induced by BCF and other Lewis acids is largely mediated by the protonation of a portion of the polymer in solution.…”
Section: Introductionmentioning
confidence: 99%